IMPACT OF RENAL TRANSPLANTATION ON ERECTILE DYSFUNCTION DUE TO CHRONIC RENAL FAILURE IN MALE PATIENTS - Ahmad, Mumtaz; Rafiuddin, Qazi; Hassan, Usman; Ahmad, Ashfaq; Husain, Sajjad (Journal of Ayub Medical College Abbottabad, 2009)
Background: Erectile dysfunction can be defined as the persistent inability of man to achieve penile erection and maintain it sufficient for satisfactory coitus. The objectives of this study were to find out the impact of successful renal transplantation on the degree and frequency of erectile dysfunction. Methods: Thirty patients of end stage renal disease that were on regular haemodialysis and candidates of renal transplantation of age range 20-55 years were included in the study after getting informed consent. Erectile functions were assessed by history, examination, investigations and international index of erectile function (IIEF) before and 3 and 6 months after renal transplantation, other information regarding disease and patient were collected in the performa. Results: Out of thirty patients 14 (46.6%) patients had sever erectile dysfunction while 16 (53.3%) patients had moderate erectile dysfunction in the pre renal transplantation period. After three months of renal transplantation 15 (50%) had severe erectile dysfunction, 6 (20%) patients moderate erectile dysfunction and 9 (30%) patients mild erectile dysfunction. After six months 11 (36.6%), 10 (33.3%) and 8 (26.6%) patients had severe, moderate and mild erectile dysfunction respectively. Conclusion: There was improvement in 40%, no change in 53.3% and deterioration in 6.6% patients in the erectile functions after getting renal transplantation for end stage renal disease. Keywords: Erectile Dysfunction, End-stage Renal Disease, International Index of Erectile Function, IIEF